Feroz-ul-Lughat (Urdu Jamay) (Ferozsons Lahore, 1980)
Feroz-ul-Lughat (Urdu Jamay) is a comprehensive Urdu dictionary that serves as an essential reference for understanding the rich vocabulary and meanings of the Urdu language.